Qaḍāyā Mahārah al-Qirā’ah li Ṭullāb Ma’had Sīmāṭarkīs bi Bāsāmān al-Sharqiyah, Dirāsah Taḥlīl Akhṭā’ fī Nuṭq al-Ḥurūf al-Hija’iyah - Rika Fitri Handayani (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
The purpose of this study was to analyze the pronunciation errors of the alphabet in the reading skills of the ninth clash students of the Simațarkis Islamic school in eastern Pasaman. The method used in this study is the method of data collection using the qualitative descriptive analytical approach. The results of this study are that the errors of pronunciation of the alphabet in the reading skill of the students of the Islamic school of Simațarkis in East Pasaman for the primary stage, the researcher found twenty letters of pronunciation errors, including the pronunciation of the letter of hā’, ‘ayn, ḥā’, ghayn, khā’, kāf, qāf, ḍād, jīm, shīn, rā’, ṭā’, dāl, tā’, Șād, zāy, Ẓā’, dhāl, thā’, fā’. One of the reasons for errors in the pronunciation of the alphabet is that the reading skill of students of the Simațarkis Islamic school in east Pasaman for the primary stage is linguistic and non-linguistic errors.من  أغراض هذه الدراسة هو تحليل أخطاء نطق االحروف الهجائية في مهارة القراءة لطلاب معهد سيماطركيس الصف التاسع ف بباسامان الشرقية. والطريقة المستخدمة في هذه الدراسة هي طريقة جمع البيانات باستخدام المنهج الوصفي النوعي التحليلي. ونتائج هذه الدراسة هي أن أخطاء نطق الحروف االهجائية في مهارة القراءة لطلاب معهد سيماطركيس بباسامان الشرقية للمرحلة الابتدائية وجدت الباحثة عشرين حرفًا من أخطاء النطق ومنه نطق حرف الهاء والعين والحاء والغين والخاء والكاف والقاف والضاد والجيم والشين والراء والطاء والدال والتاء والصاد والزاي والظاء والذال والثاء والفاء. من أسباب الأخطاء في تلفظ الحروف الهجائية أن مهارة قراءة طلاب معهد سيماطركيس بباسامان الشرقية اللمرحلة الابتدائية أخطاء لغويًة وغير لغوية.